(untitled) (Indian Journal of Veterinary Pathology, 2024)
Fungal infections can constitute a major health concern for the pets. In tropical nations like India, superficial fungal infections are quite widespread and vary in incidence throughout time and region. Fusarium species are common soil saprophytes and plant pathogens and produce toxins that can contaminate stored grain. In the present study, a total of 150 cats belonging to different age groups and breeds were examined for cutaneous lesions. Skin scrapping and hair samples were collected from cats with cutaneous lesions and preliminarily examination was done with 10% KOH preparation mount. The samples were further cultured for fungal identification into both Sabouraud’s dextrose agar (SDA) with 0.05% chloramphenicol and 0.5% cycloheximide, and dermatophyte test medium (DTM). Three cats with a clinical finding of itching, scratching, itching, hair loss, multiple alopecic lesions all over the body, crust formation, and erythematous lesions were diagnosed with Fusarium spp. infection. From the colonies in SDA, Lactophenol cotton blue staining was done for the fungal identification that revealed characteristic fusarium macroconidia having foot-shaped basal cells and pointed fusiform, with multiple transverse septa confirming the presence of Fusarium spp. infection in the cat.